Smg1 Nonsense Mutations Do Not Abolish Nonsense-Mediated mRNA Decay in Drosophila melanogaster - Chen, Zhenzhong (Copyright © 2005 by the Genetics Society of America, 2005)
Smg1 is a key component of nonsense-mediated decay (NMD) in Caenorhabditis elegans and mammals. Here we report that two nonsense alleles of the ortholog of Smg1 do not affect NMD in Drosophila melanogaster.